2006
DOI: 10.1063/1.2155386
|View full text |Cite
|
Sign up to set email alerts
|

Mimicking solvent shells in the gas phase. II. Solvation of K+

Abstract: The observed gas-phase coordination number of K+ in K+(H2O)m clusters is smaller than that observed in bulk solution, where the coordination number has been reported to be between 6 and 8. Both theoretical and gas-phase studies of K+(H2O)m cluster ions point to a coordination number closer to 4. In the gas phase, the coordination number is determined by a variety of factors-the most critical being the magnitude of the K+...ligand pairwise interaction. Decreasing the magnitude of the ion...ligand interaction al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
41
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 25 publications
5
41
0
Order By: Relevance
“…In order to fully solvate an ion in the solvation shell, usually six water molecules are needed. [70,71,72,75] At such high bulk concentration as 5M the cations and anions are very close to each other. However, our SHG data of the five salts KF, KCl, KBr, NaBr and NaCl did not show the same ion pairing or association effects as the NaF salt.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In order to fully solvate an ion in the solvation shell, usually six water molecules are needed. [70,71,72,75] At such high bulk concentration as 5M the cations and anions are very close to each other. However, our SHG data of the five salts KF, KCl, KBr, NaBr and NaCl did not show the same ion pairing or association effects as the NaF salt.…”
Section: Resultsmentioning
confidence: 96%
“…Studies showed that these different behaviors were largely due to their different hydration number and hydration free energies. [69,70,71,72] Recently, using SFG vibrational spectroscopy, Cremer and co-workers investigated the ion effects on the water molecules at the polymer surfactant aqueous interfaces. [73,74] In these studies, significant anion effects and insignificant cation effect were observed.…”
Section: Resultsmentioning
confidence: 99%
“…In this cooperative process, the movement of the water molecule at the short end leads to the formation of a cyclic structure, where the two water molecules and the HONO species act as hydrogen-bond acceptors and form a complete solvation shell around the H 3 O + ion. The formation of such a solvation shell can effectively stabilize the central H 3 O + ion, a well-established fact in the gas-phase reaction involving ionic clusters (23)(24)(25)(26). Due to the stabilization effect, the formation of HONO-containing isomer 4-ii, from the highly populated isomer 4E, entails a low-energy barrier of ∼2.1 kcal/mol.…”
mentioning
confidence: 99%
“…According to this picture, it shall be hard to imagine how such longrange interactions can be so different for the Na + and the K + cations, since people already knew that the solvation of the Na + and the K + cations hardly go beyond the second solvation shell. [57,58] On the other hand, in the currently prevalent paradigm, the adsorption of the more polarizable anions to the aqueous solution surfaces should be enhanced, but not the less polarizable anions, such as the F − , and the cations, such as the Na + and the K + cations.Then the difficulties shall be the same as in the classical picture on how the significantly different Na + and the K + cation effects are originated.Richmond and co-workers observed the change of the SFG spectra for the NaF aqueous solution surfaces, [24] which is further confirmed in our measurement as reported here.They concluded that even though the F − anion concentration was 'diminished' in the top surface water layers, the presence of F − anion in the surface region can still affect the hydrogen bonding structure of the water molecules in the surface region in different ways from the larger and more polarizable Br − and I − anions. According to the same reasoning as Richmond and co-workers proposed for the F − anion, the presence of the Na + and the K + cations in the surface layers, even though diminished from the bulk concentration, can also be expected.…”
mentioning
confidence: 99%
“…According to this picture, it shall be hard to imagine how such longrange interactions can be so different for the Na + and the K + cations, since people already knew that the solvation of the Na + and the K + cations hardly go beyond the second solvation shell. [57,58] On the other hand, in the currently prevalent paradigm, the adsorption of the more polarizable anions to the aqueous solution surfaces should be enhanced, but not the less polarizable anions, such as the F − , and the cations, such as the Na + and the K + cations.…”
mentioning
confidence: 99%